The disregard of human rights in the globalization strategy (an alternative society perspective) - Hinkelammert, Franz (2016)
Human rights foundations in today’s world are discussed. The author presents the thesis that there has been a profound change on how human rights are viewed by the economic and political powers due to the so-called globalization strategy, which, in fact, is an overall market strategy.The author also analyzes the constituent features of the Social State after World War II and how dominant sectors currently perceive its key elements as left-wing politics. The former is added to the replacement of democracies controlled by Security States, particularly in Latin America, from the Chilean military coup in 1973 to the end of the 20th century. This proves that neo-liberal capitalism cannot be sustained in the long run if it is not treated as a total market system held by ideologies of National Security and their respective armies.The new alternative society projects that have emerged in Latin America exactly respond to the market totalitarianism promoted by neo-liberalism.